1993
DOI: 10.1097/00006123-199310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Versus Postoperative Neuropsychological Sequelae of Arteriovenous Malformations

Abstract: In a cohort of 14 patients suffering from cerebral arteriovenous malformations (AVM), neuropsychological functioning was examined before and after AVM resection. Improvements after surgery were assumed to be due to enhanced neurocognitive functions associated with the hemisphere ipsilateral to the AVM, and to a lesser extent, with the contralateral hemisphere. Before surgical intervention, the performances of AVM patients were deficient relative to matched normals. Postoperatively, neuropsychological gains wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The AVM is eliminated by gradually evolving radiation effects [3] . Compared to the patient cohort of conventional surgery, as reported by Mahalick et al [12] , the postoperative cognitive condition of patients receiving radiosurgery should be different. In a long-term postradiosurgical follow-up, Riva et al [13] found normal neurobehavior of 8 AVM patients an average of 6 years after radiosurgery.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The AVM is eliminated by gradually evolving radiation effects [3] . Compared to the patient cohort of conventional surgery, as reported by Mahalick et al [12] , the postoperative cognitive condition of patients receiving radiosurgery should be different. In a long-term postradiosurgical follow-up, Riva et al [13] found normal neurobehavior of 8 AVM patients an average of 6 years after radiosurgery.…”
Section: Discussionmentioning
confidence: 87%
“…On the contrary, Blonder et al [11] examined 10 AVM patients with neuropsychological tests and found a slightly impaired function compared to normal controls. Mahalick et al [12] found neuropsychological impairment in all of their 24 patients prior to surgical treatment and reported that roughly 50% had improved after surgery. In radiosurgery no real 'open surgery' is performed.…”
Section: Discussionmentioning
confidence: 99%
“…This shows the clinical potential of ASL for therapeutic evaluation of WM perfusion deficits, again showing the clinical potential of ASL. The occurrence of perfusion deficits in tissue near an AVM has been described in the literature and may be related to the so-called steal phenomenon: a high flow volume shunted through an AVM fistula may induce a decrease in cerebral perfusion pressure in surrounding brain tissue (26). However, as evidenced by DSC-MRI, the hypointense area on the ASL scans is most probably caused by an increased transit time rather than hypoperfusion.…”
Section: Discussionmentioning
confidence: 98%
“…Cognitive deficits in patients with AVMs may be present in 60 to 80% of cases (Gomez-Tortosa et al 1995;Mahalick et al 1993). The majority of the literature describes patients with ruptured AVMs, many of whom present with seizures, however, studies investigating the specific effects of seizures on neuropsychological profile in these patients are generally not available.…”
Section: Vascular Malformationsmentioning
confidence: 99%